2013
DOI: 10.1136/amiajnl-2012-001557
|View full text |Cite
|
Sign up to set email alerts
|

ICD-9 tobacco use codes are effective identifiers of smoking status

Abstract: Researchers should not be deterred by the unavailability of full-text records to determine smoking status if they have ICD-9 code histories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 21 publications
1
89
0
Order By: Relevance
“…Several studies have reported that CYP2A6*2 and other genotypes associated with poor nicotine metabolizer status correlate with a decrease in cigarettes per day [54]. These results validate a previous study that demonstrated that ICD-9-CM codes can be markers of smoking behavior in EHRs [55].…”
Section: Replicating Associationssupporting
confidence: 86%
“…Several studies have reported that CYP2A6*2 and other genotypes associated with poor nicotine metabolizer status correlate with a decrease in cigarettes per day [54]. These results validate a previous study that demonstrated that ICD-9-CM codes can be markers of smoking behavior in EHRs [55].…”
Section: Replicating Associationssupporting
confidence: 86%
“…Previous studies have shown that ICD-9 tobacco use codes (305.1 and V15.82) can be used effectively to identify smoking status (Wiley, Shah, Xu, & Bush, 2013), and any smoking-related ICD-9 code during the blackout period was coded as having smoked at baseline. Similarly, individuals with ICD-9 code 278.0 during the blackout period were coded as being obese at baseline.…”
Section: Covariatesmentioning
confidence: 99%
“…We included smokers, defined on the basis of an International Classification of Diseases, Ninth Revision, Clinical Modification ( ICD‐9‐CM ) diagnosis code of 305.1, which has previously been validated and found to have fair sensitivity but high specificity for active smoking 16. Among these patients, we evaluated those who were admitted with a principal diagnosis of MI ( ICD‐9 410.x) or received percutaneous coronary intervention (PCI; ICD‐9 36.06, 36.07, or 36.09) or coronary artery bypass graft (CABG) surgery ( ICD‐9 36.1x).…”
Section: Methodsmentioning
confidence: 99%